Efektivitas Pemberantasan Tindak Pidana Judi Online - Rian Ardiansyah, Maruf; Sudarmanto, Kukuh; Sukarna, Kadi; Arifin, Zaenal (Journal Juridisch, 2023)
The purpose of this research is to analyze the effectiveness of combating online gambling crimes in the jurisdiction of the Central Java Regional Police (Polda Jawa Tengah). This research is important because of the increasing prevalence of online gambling, or what is more commonly known as illegal lottery gambling (togel), which has become a significant issue across all layers of Indonesian society. The research methodology used is socio-legal. The novelty of this research lies in examining the effectiveness of combating online gambling within the jurisdiction of the Central Java Regional Police. The findings of this study explain that the factors influencing individuals getting involved in online gambling can be divided into two categories: internal and external factors. The application of Article 303 paragraph (1) of the Indonesian Criminal Code (KUHP) for conventional gambling and Article 45 jo. Article 27 paragraph (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE) is discussed. Various methods can be employed for the prevention of online gambling, including pre-emptive, preventive, and repressive methods. The prevention of online gambling is an effective means of combating online gambling crimes. Tujuan penelitian ini untuk menganalisis efektivitas pemberantasan tindak pidana judi online di wilayah hukum Polda Jawa Tengah. Penelitian ini penting karena semakin maraknya judi online atau yang lebih dikenal perjudian togel gelap (togel) yang saat ini marak menjadi salah satu permasalahan yang cukup signifikan disoroti di semua lapisan masyarakat Indonesia. Metode penlitian menggunakan yuridis sosiologis. Kebaruan penelitian ini adalah mengkaji efektifitas pemberantasan judi online di wilayah hukum Polda Jawa Tengah. Hasil penelitian ini menjelaskan bahwa faktor yang mempengaruhi masyarakat terjerat judi online antara lain terbagi menjadi dua faktor, yaitu faktor internal dan faktor eksternal. Penerapan Pasal 303 ayat (1) KUHP untuk judi konvensional maupun Pasal 45 jo. Pasal 27 ayat (2) Undang-undang Nomor 11 Tahun 2008 tentang ITE. Upaya pencegahan judi online dapat dilakukan berbagai cara antara lain dengan metode pre-emptive, metode preventif dan metode represif. Metode pencegahan perjudian online merupakan sarana yang efektif dalam pemberantasan tindak pidana judi online.